Induction of excessive endoplasmic reticulum stress in the Drosophila male accessory gland results in infertility. - Chow, C.Y.; Avila, F.W.; Clark, A.G.; Wolfner, M.F. (PLoS ONE, 2015)
Endoplasmic reticulum (ER) stress occurs when misfolded proteins accumulate in the lumen of the ER. A cell responds to ER stress with the unfolded protein response (UPR), a complex program of transcriptional and translational changes aimed at clearing misfolded proteins. Secretory tissues and cells are particularly well adapted to respond to ER stress because their function requires high protein production and secretory load. The insect male accessory gland (AG) is a secretory tissue involved in male fertility. The AG secretes many seminal fluid proteins (SFPs) essential for male reproduction. Among adult Drosophila tissues, we find that genes upregulated by ER stress are most highly expressed in the AG, suggesting that the AG is already undergoing high levels of ER stress due to its normal secretory functions. We hypothesized that induction of excessive ER stress in the AG above basal levels, would perturb normal function and provide a genetic tool for studying AG and SFP biology. To test this, we genetically induced excessive ER stress in the AG by conditional 1) expression of a misfolded protein or 2) knockdown of the UPR regulatory protein, BiP. Both genetic manipulations induced excessive ER stress in the AG, as indicated by the increase in Xbp1 splicing, a marker of ER stress. Both models resulted in a large decrease in or loss of SFP production and male infertility. Sperm production, motility, and transfer appeared unaffected. The induction of strong ER stress in the insect male AG may provide a simple way for studying or manipulating male fertility, as it eliminates AG function while preserving sperm production.